Ionic regulation of mycobacterial infection by potassium and potassium channel - Lim, Carey Fang Hui (Nanyang Technological University, 2022)
Epigenetic analysis of monocytes from active TB patients demonstrated enrichment of KCNJ15, which encodes an inwardly rectifying K+ channel (Kir4.2). We investigated the function of Kir4.2 in mycobacterial infection using a gain and loss-of-function approach and knockout mouse model. Kir4.2 was observed to promote inflammation and apoptosis and led to changes in immune populations in the lung and their ability to control bacterial burden. Additionally, we found that the necrotic mycobacterial granuloma microenvironment possessed a high K+ milieu. Exploring the effects of high extracellular K+ ([K+]e) on monocytes revealed that K+ influx resulted in mitochondrial dysfunction-induced autophagic bacterial killing. Thus, this study investigated the role of KCNJ15/Kir4.2 and high [K+]e on the acute host immune response against mycobacterial infection, which may inform future potassium-targeting host-directed therapeutics.